Relation and influences of sports climbers' specific strength on the success in sports climbing - Stankovic, D.; Joksimovic, A.; Aleksandrovic, M. (South African Journal for Research in Sport, Physical Education and Recreation, 2011)
The aim of this research was to determine relations to, and influences of the specific strength of sport climbers on success in sport climbing. Research was conducted on a sample of sport climbers (N=32), participants in the Balkan championships "Naissus Route Climbing Challenge 03", competing on national and international level, by the application of nine tests for the estimation of sport climbers' specific strength and three variables for the estimation of success in sport climbing. Relations were determined by means of canonical correlation analysis and the influences by means of a regression analysis. The results of the research show that success in sport climbing depends on specific strength, mostly specific static strength. All variables have statistically significant projections on the canonic factor, most of all variables of specific static strength - block under 90° angle (BL90), block under 90° angle on left hand (B90L) and block under 90° angle on right hand (B90R) and variables of the situational-motor explosive strength - maximal reach with left hand (MRLH), maximal reach with right hand (MRRH) and maximal reach with both hands (MRBH) and pull-ups with two fingers (PU2F). Also, it can be concluded that specific strength significantly influences the success in all three criteria - the most difficult climbed route up to now (MDCR), the most difficult climbed route this season (MDDS) and competition standings (COST). However, none of the variables individually significantly influenced the most difficult climbed route up to now (MDCR); two variables - maximal reach with right hand (MRRH) and block under 90° angle (BL90) - influenced the most difficult route climbed this season (MDDS); and two variables for the estimation of static strength - block under 90° angle (BL90) and block under 90° angle on left hand (B90L) - influenced competition standings (COST). The obtained results can be utilised for the selection and direction of young talent towards sport climbing.